Quantification of biogenic silica by means of Fourier transform infrared spectroscopy (FTIRS) in marine sediments - Vogel, Hendrik; Meyer-Jacob, Carsten; Thöle, Lena; Lippold, Jörg; Jaccard, Samuel L. (Limnology and oceanography. Methods, 2016)
Due to the major role played by diatoms in the marine biological pump, opal/biogenic silica (bSi) has a strong potential as a proxy for paleoproduction reconstructions. Here, we present a detailed evaluation of the independent Fourier transform infrared spectroscopy (FTIRS) calibration introduced by Meyer-Jacob et al. (2014a), which is based on synthetic sediment mixtures with known concentrations of bSi and the application of partial least squares (PLS) regression, for the determination of bSi in marine sediments. To test the robustness of the FTIRS calibration for marine samples we selected 199 globally distributed samples, with available wet chemically inferred bSi concentrations and compared the results of both methods. We observe that the spectral characteristics in marine samples are comparable to those reported for a synthetic FTIR spectrum composed solely of spectral features in quartz, biogenic silica, and calcite. FTIRS-inferred and wet-chemically measured bSi concentrations for the set of 199 marine sediment samples are strongly correlated (R2 = 0.87; RMSE = 5.27%). Together with the high reproducibility of bSi values by the independent calibration our results corroborate the applicability of the independent FTIRS bSi calibration for quantification in marine samples. This together with the succinct sample preparation procedure, rapid analysis, reduced consumable and machine maintenance costs makes FTIRS a powerful and robust alternative for the quantitative analysis of bSi in marine sediments.
Gesehen am 28.07.2021